2003
DOI: 10.1128/jcm.41.9.4038-4042.2003
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Decrease with Age of Helicobacter pylori Seroprevalence among Swedish Blood Donors

Abstract: Blood donors are often used as proxies for the general population in studies of Helicobacter pylori epidemiology. Our aim was to test if the age-specific seroprevalence rates among blood donors match with the corresponding rates in a random population sample. This descriptive study was based on sera obtained from 3,502 blood donors representing all Swedish counties and cities. An age-stratified random population sample of 1,030 from Stockholm County served as comparison. Sera were analyzed by an in-house enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 35 publications
2
17
1
Order By: Relevance
“…We examined IgG and IgA responses to H. pylori WC antigens, and IgG responses to a strain-specific antigen (CagA), and to a conserved but host-specific antigen (HspA) (13). Nevertheless, considering a relatively homogeneous population, as in this Finnish village, aids analysis, and H. pylori prevalence results are consistent with studies of other western adult populations (47, 48). Although the sample was moderate in size, the study design was able to demonstrate stability of antibodies over a 21-year period, as we have documented using other measurements in another study of this same population (25).…”
Section: Discussionsupporting
confidence: 88%
“…We examined IgG and IgA responses to H. pylori WC antigens, and IgG responses to a strain-specific antigen (CagA), and to a conserved but host-specific antigen (HspA) (13). Nevertheless, considering a relatively homogeneous population, as in this Finnish village, aids analysis, and H. pylori prevalence results are consistent with studies of other western adult populations (47, 48). Although the sample was moderate in size, the study design was able to demonstrate stability of antibodies over a 21-year period, as we have documented using other measurements in another study of this same population (25).…”
Section: Discussionsupporting
confidence: 88%
“…A Spanish study showed less infected individuals in the oldest age groups (>75 years), but these groups consisted of fewer participants . In a Swedish study, the prevalence of H. pylori infection among blood donors was lower after the age of 50 …”
Section: Resultsmentioning
confidence: 96%
“…In China, H. pylori prevalence has been reported as high as 83.4% . Additionally, many countries such as China, Japan and Bulgaria have experienced an overall increase in the prevalence of H. pylori infection over the last 20 years (Figure ) . In Canada, the prevalence of H. pylori is approximately 30%; however, within the Aboriginal populations living in Canada, the prevalence of H. pylori has been reported as high as 95% .…”
Section: Prevalence Of H Pylori Infectionmentioning
confidence: 99%